When Your Partner Cheats: Financial Infidelity in Committed Couples - Michael D. Mong; Hans Stadthagen; Kenji Noguchi; Michelle Jeanfreau (Journal of Financial Therapy, 2021)
The present study evaluated the affective, behavioral, and cognitive responses of 203 participants who were queried about their romantic partners’ potential financial infidelity as well as their own. Results were analyzed through the lens of the ABC model (affect, behavior, cognition) and indicated that participants would be much more upset and less accepting if their romantic partner: filed for bankruptcy without their partner’s knowledge, gambled away money without telling their partner, lied to cover up a debt, kept a secret account, took out savings without consulting their partner, spent money on pornographic material without telling their partners, hid credit card statements, or kept a raise or a bonus secret. Further, the only behavior that elicited a willingness to leave the relationship was filing for bankruptcy without informing the romantic partner. Clinical implications and future research directions are also discussed.
Keywords: financial infidelity